Calycosin pretreatment enhanced the therapeutic efficacy of mesenchymal stem cells to alleviate unilateral ureteral obstruction-induced renal fibrosis by inhibiting necroptosis - Qiongdan Hu; Bingwen Zhu; Guoqiang Yang; Jian Jia; Honglian Wang; Ruizhi Tan; Qiong Zhang; Li Wang; Fahsai Kantawong (Elsevier, 2023)
Bone marrow-derived mesenchymal stem cells (MSCs) show antifibrotic activity in various chronic kidney diseases. Here, we aimed to investigate whether Calycosin (CA), a phytoestrogen, could enhance the antifibrotic activity of MSCs in primary tubular epithelial cells (PTECs) induced by TGF-β1 and in a mouse model of unilateral ureteral obstruction (UUO). We found that MSCs treatment significantly inhibited fibrosis, and CA pretreatment enhanced the effects of MSCs on fibrosis in vitro. Consistent with the in vitro studies, MSCs alleviated tubular injury and renal fibrosis in mice after UUO, and CA-pretreated MSCs resulted in more significant improvements in tubular injury and renal fibrosis than MSCs after UUO. Moreover, MSCs treatment significantly inhibited necroptosis by repressing the elevation of MLKL, RIPK1, and RIPK3 in PTECs treated by TGF-β1and in mice after UUO, and CA-pretreated MSCs were superior to MSCs in alleviating necroptosis. MSCs significantly reduced TNF-α and TNFR1 expression induced by TGF-β1 in PTECs and inhibited TGF-β1, TNF-α, and TNFR1 expression induced by UUO in mice. These effects of MSCs were significantly enhanced after CA pretreatment. Therefore, our results suggest that CA pretreatment enhances the antifibrotic activity of MSCs by inhibiting TGF-β1/TNF-α/TNFR1 signaling-induced necroptosis.